Phenozan Influence on the Physiological-Biochemical Parameters of the Young Minks Leading to Their Advanced Properties - Balakirev, Nikolai A.; Zaitsev, Sergei Yu.; Rizvanov, Albert A. (International Journal of Zoology, 2016)
The antioxidant influence on the physiological-biochemical parameters of productive animals is one of the most important directions in modern animal science. Phenozan is a synthetic antioxidant with high biological activities including those for animals. The positive effects of phenozan on the physiological-biochemical parameters of the mink blood were found. These effects are leading to the intensive growth, strong health, enhancement of the mink fur quality, and so forth. The total amount of the erythrocytes in the mink blood increased by about 4-5% due to phenozan inclusion in the mink diet. Even a more significant increase was found in hemoglobin content in the mink blood and erythrocytes (by about 9.5% and 8.8%, resp.) due to phenozan inclusion of 100 mg/day, whereas it was found only by about 6.1–5.3% or 5.5–0.3%, owing to phenozan inclusion of 50 or 150 mg/day. For many other parameters the optimal phenozan concentration was about 100 mg/day per head according to the result obtained for all studied animal groups. Thus, phenozan can be successfully used as a biologically active compound for mink nutrition and is recommended for other farm animals.